Comparative analysis of elite football players' throw-in - Zahalka, F.; Maly, T.; Mala, L.; Buzek, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Lees and Nolan (1998) state that a throw-in is on the one hand a means of initiation of a game (a ball got out of playing field across a side line) and on the other hand it is a player`s tactic skill. On professional level, but very often on amateur level, every team has its own specialist in throw-in on long distances, into opponents` penalty area. This way of throw-in in attack zone is more accuracy than long high pass of the ball. Methods The research group was n=13 (age = 20.28±0.91 years, height = 179.45±4.62 cm and weight = 76.15±3.72 kg). To evaluate the distance of the throw-in, 2D analysis was used; it was provided by one camera covering calibrated scope of 30m. 3 cameras were used for 3D spatial analysis of player`s movement. The speed of the thrown ball was measured by means of a radar device STALKER ATS at the same time. Results The observed parameters of throw-in in the players show a longer distance (the length of throw-in) when throwing after a run up that in throwing from a standing position. In throw-in from a standing position an average value of the longest measured trials was xds = 20.19 ± 1.52 m. In throw-in after the run up, the distance of the throw was longer about 13.5 % when compared to throw-in from the standing position (xdr = 23.34 ± 2.75 m). In case of maximal velocity of the ball after the throw-in, the lower average speed was registered in throw-in from the standing position vs = 50.1 km/h than in the throw-in after run up vr = 53.9 km/h. The highest registered speed after throw-in from the standing position was vsmax = 56.2 km/h and the minimal speed was vsmin = 42.2 km/h. Variation coefficient of the speed of all trials is 6.6 %. When throwing-in after run up the maximal measured velocity was vrmax = 62.3 km/h and the minimal velocity was vrmin = 46.9 km/h. The performance of throw-in after run up is realized in two ways. In a symmetric way, both arms perform symmetric movement above a head in a final phase. In an asymmetric way, a trunk is more twisted. A non-dominant arm is shifted forward and a swipe is performed by a dominant arm. From totally 13 players, 7 players performed the throw-in asymmetrically and 6 players symmetrically. Conclusion Measured data show wider scope of values among several players. It proves different level of technical mastery of particular skill. Linthorne and Everett (2004) indicate variable velocity in various angle of the throw-in from the standing position in range 43.2 - 68.4 km/h in an experienced player. In training practice it is necessary to focus on improvement of performance of this skill and the choice of suitable way of the throw-in. References Lees A, Nolan L. (1998). The biomachanics of soccer: A review. Journal of Sports Science, 16, 211-234. Linthorne NP, Everett DJ. (2004). Release Angle for Attaining Maximum Distance in the Soccer Throw-in. Sport Biomechanice, 5,243-260. This study was supported by MSM 0021620864 & GACR 406/08/1514